2020
DOI: 10.1111/ijd.14766
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Th17‐ and Treg‐specific transcription factors in vitiligo patients

Abstract: Background Vitiligo is mainly considered an autoimmune skin disease as the number of IL‐17 producing Th17 cells, involved in the development of autoimmune and inflammatory pathologies, increased in vitiligo skin. T regulatory cells (Tregs) seem to be altered during the disease. Thus, there must be some upstream molecular factors that regulate the cellular response to apoptotic and inflammatory stimuli. Objectives To investigate the expression of Th17‐ and Treg‐specific transcription factors in PBMCs and to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…In our study, the mean age of vitiligo onset was 26.5 ± 8.3 years. This is in accordance with the finding of Bhardwaj et al (15) who reported that the mean age at onset of vitiligo was 20.8 ± 10.0 years. On the contrary, Martins et al (16) have found that the average age of onset of nonsegmental vitiligo was 6.1 ± 3.1years.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the mean age of vitiligo onset was 26.5 ± 8.3 years. This is in accordance with the finding of Bhardwaj et al (15) who reported that the mean age at onset of vitiligo was 20.8 ± 10.0 years. On the contrary, Martins et al (16) have found that the average age of onset of nonsegmental vitiligo was 6.1 ± 3.1years.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, our meta-analysis suggested the role of decreased FOXP3 expression in disease activity of vitiligo (Figure S1a ). These results were in concordance with the previous studies [ 5 , 9 , 17 20 , 22 , 24 26 ]. The decreased FOXP3 protein and transcript levels in the blood may be due to the reduced Tregs' frequency in vitiligo patients; therefore, our meta-analysis further suggests for the role of decreased Tregs' frequency in vitiligo pathogenesis.…”
Section: Discussionsupporting
confidence: 94%
“…Forkhead box P3 (FOXP3) is a key transcription factor of Tregs; it regulates the production of Tregs' suppressive molecules such as TGF- β , CTLA-4, IL-10, and GITR [ 23 ]. However, FOXP3 expression has been found to be altered in vitiligo patients [ 5 , 9 , 17 20 , 22 , 24 26 ]. Additionally, IL-10 and TGF- β , the key immunosuppressive cytokines produced by Tregs, govern the development of iTreg cells and participate in peripheral tolerance preservation and peripheral Treg cell maintenance [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In turn, these innate immune cells and APCs recruit auto-reactive T cells to mediate specific destruction of melanocytes in vitiligo (10). The loss of tolerance to self-antigens also involves reduced cutaneous regulatory T cell (Treg) activity (11,12). Tregs are subsets of T cells responsible for peripheral tolerance via suppression of immune cells, including self-reactive, cytotoxic T cells, to maintain immune homeostasis (13).…”
Section: Introductionmentioning
confidence: 99%